Determinasi Minat Beli pada Industri Kecil Menengah di kota Malang - Mochammad Lukman Zaini Kurniawan (Universitas Diponegoro, 2020)
This study aims to determine the extent to which the variable store image, trust and brand recognition influences the purchase intention of consumers at SME’s in Malang city. The location of research are two shops in the Sanan area that produce tempe chips, two stores in the Pandanwangi area that produce corn chips, one store in the Polowijen area and one store in Ciliwung that produces fruit chips. The population is all consumers that can’t known with certainty. Samples are consumers who visited in six stores. The sampling technique is purposive sampling. Data analysis using SEM GSCA. The results of this study are (1) store image has a positive not significant correlation on trust; (2) store image has a positive significant correlation on purchase intention; (3) store image has a positive significant correlation on brand recognition; (4) brand recognition has a positive significant correlation on trust; (5) brand recognition has a positive not significant correlation on purchase intention; (6) trust has a positive significant correlation on purchase intention; (7) store image has a positive significant correlation on purchase intention through in trust.